APPLICATION OF SNOWBALL THROWING MODEL TO IMPROVE STUDENTS' LEARNING OUTCOMES IN THE MATERIAL OF SPATIAL BUILDINGS IN GRADE II OF STATE ELEMENTARY SCHOOL 22 BANDA ACEH - Ramadhani, Citra Suci; Fauzi, Fauzi; Yamin, M. (Universitas Syiah Kuala, 2024)
Abstrak (English)The use of appropriate student learning models was very important, because it can be improved the student learning outcomes. Therefore, the researcher was conducted a study related to teaching the snowball throwing model. Where before, the teachers snowball throwing model was more prominent that the students. The formulation of the problem was how were student learning activities and student learning outcomes by applying the snowball throwing learning model of spatial recognition material in class II SD Negeri 22 Banda Aceh. The purpose of this research was to be found student activities and student learning outcomes by applying the snowball throwing learning model to the material for introducing spatial shapes in Class II SD Negeri 22 Banda Aceh. The approach used in this study was a qualitative approach, namely the type of research used was Classroom Action Research. In this study, the population was all class II SD Negeri 22 Banda Aceh, while the samples in this were all class II with a total of 30 student. The research was conducted for 2 days with data collection techniques, namely pre-test, pos-test, cycle I and cycle II. Data analysis technques were used the avarage value of the pre-test, pos-test and student activity tables. Then the results of this study, where before using the snowball throwing model obtained data from 7 students (23.33%) who obtained a score of 75 and above, with an average value of 66 and this was stated that they had not yet reached the Minimum Completeness Criteria, but after using the snowball throwing model in class II class material, student learning outcomes have increased. In the first cycle test, there were 11 students (35.7%) who scored 75 and above with an average score of 69.66%. furthermore, there was an increase again after the second cycle test was carried out, there were 26 students (86.66%) who obtained a score of 75 and above with an average percentage score of 85.66%.